Thermal transfer analysis of tubes with extended surface with fractal design (2018)
Heat exchangers are formed by tubes with extended surfaces that improve the transfer of heat between two media (e.g., a solid and a liquid in motion). This paper presents the design of an extended surface tube with fractal geometry, corresponding to the Koch snowflake and the Cesaro curve. For the design, we used the CAD computational tool, and afterwards we performed the CAE finite element analysis and verified the thermal behavior of the designed tube. We were able to reduce the heat transfer time and increase the heat flow in the system in the following manner: for smooth tube, 250 W/m2; for Koch surface, 500 W/m2; for six fins, 1450 W/m2; and for Cesaro curve, 3600 W/m2. These results demonstrate the limits of the design and the advantages of its implementation in machinery such as condensers, heat exchangers, and boilers.